PENGARUH MODEL INDUKTIF KATA BERGAMBAR TERHADAP PRESTASI PEMBELAJARAN KOSA KATA PADA SISWA TAHUN PERTAMA DI MTS AL FAJAR PEKANBARU - Susanna, Susanna; Afrianto, Afrianto; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is aimed at finding out the effect of Picture Word Inductive Model (PWIM) on vocabulary learning achievement of the first year students of MTs Al Fajar Pekanbaru in academic year 2017/2018. The data were collected on April. The population of this research is the first year students of MTs Al Fajar Pekanbaru. The number of sample is 34 students selected by using cluster random sampling technique. This research is a pre experimental research with one group pre-test post-test design. The instruments to collect the data were multiple choice test with 25 questions and matching word test with 10 questions. The result of the data analysis showed that the mean score of pre-test is 58.65 while in post-test is 76.22. It showed us that the mean score of post-test was higher than pre-test. Hence, there is a significant effect of Picture Word Inductive Model (PWIM) on students' vocabulary learning achievement. In other words, the alternative hypothesis of this research, “There is any significant effect of Picture Word Inductive Model (PWIM) on the vocabulary learning achievement of the first year students of MTs Al Fajar Pekanbaru'' is accepted and the null hypothesis is rejected. It can be inferred that teaching vocabulary by using Picture Word Inductive Model (PWIM) as one of the alternative strategies has an effect on the students’ vocabulary learning achievement.Keywords: PWIM, Vocabulary, Learning Achievement.